St. Catherine of Alexandria in Renaissance Roman art: case studies in patronage - Stollhans, Cynthia (Ashgate, 2014)
From East to West: St. Catherine of Alexandria arrives in Rome -- The 'Romanization' of St. Catherine and the cardinal from Milan -- St. Catherine of Alexandria and the papacy -- Sacred and gendered unions: Catherine of Alexandria and hermit saints -- A problem of two saints named Catherine in the Fetti Chapel -- In the service of family dynasties: the Theodoli and Cesi